Predicting parents' use of booster seats. Issue 5 (17th March 2011) - Bruce, Beth S; Snowdon, Anne W; Cunningham, Charles; Cramm, Carolyn L; Whittle, Krista; Correale, Heather; Barwick, Melanie; Piotrowski, Caroline; Warda, Lynne; Harrold, Jessie
Abstract : Objective: To examine the simultaneous contribution of multiple factors associated with parents' use of booster seats. Methods: Using the theory of planned behaviour framework, constructs of the theory were tested for usefulness in predicting self-reported intent and behaviour with respect to parents' use of booster seats. Through the use of structural equation modelling, the study demonstrated the most significant predictors of the intent to use a booster seat and reported use of booster seats in a Canadian sample (n=1480) of parents of school-aged children, 4–9 years. Results: The strongest predictors of intent to use booster seats were attitudes (benefits of booster seat use) and second, subjective norms (perceived booster seat use in the community). Parent barriers were inversely associated with intent and use of booster seats and child barriers with use. Intent and norms had the greatest effect on use, both positive and equally influential. The final model explains 30% of the variance in booster seat use. Conclusion: Messages that address the benefit to the child in preventing injury could be beneficial if spread more diversely, establishing a social norm. Legislation, enforcement and local policy could positively influence the perceived culture that supports and expects booster seat use for school-aged children.